Promoting Expertise Through Simulation (PETS): A conceptual framework. (December 2022) - Jossberger, Helen; Breckwoldt, Jan; Gruber, Hans
Abstract: Questioning how and why simulations can be suitable for supporting intraindividual learning and expertise development motivated this study. We depart from an empirically well supported cognitive perspective of expertise that focusses on cognitive adaptations through long-term engagement with professional work activities. The strength of simulation learning is seen in its multiple explanatory base, which is used to build the framework PETS (Promoting Expertise Through Simulation). The PETS model specifically addresses how simulations can contribute to intraindividual knowledge restructuring through case processing and learner-tailored guidance of a trainer supporting the thorough engagement in deliberate practice activities to go beyond automatization. Preparation, briefing, repetitive practice opportunities, and debriefing are phases of instructional embedding in simulation learning for which the PETS model identifies important prerequisites to enhance understanding of what works for whom under which conditions and why during expertise development. Highlights: Multiple explanatory base for why simulations can support intraindividual learning. PETS model focusses on experience-based knowledge restructuring. PETS model stresses the role of learner-tailored guidance by a qualified trainer. PETS model provides a trajectory for a more efficient use of simulation. PETS model contributes to enhanced understanding of expertise development.